Image-assisted textural analysis of plagioclase crystals in volcanic rocks: an application to lavas erupted on 2021 at Pacaya volcano, Guatemala - Visalli, Roberto; Giuffrida, Marisa; Cardone, Massimiliano; Costa, Giorgio; Ortolano, Gaetano; Viccaro, Marco (Frontiers in Earth Science, 2025)
The adoption of semi-automated image processing methods to investigate geo-petrological processes has grown quickly in recent years. Utilizing multivariate statistical analysis of X-ray maps, these methods effectively extract quantitative textural, chemical, and modal parameters from selected thin sections or micro-domains in volcanic samples whose constituents can show peculiar textures due to the magmatic processes involved. In this study, we have processed X-ray maps of major elements from the 2021 basaltic lava rocks of Pacaya volcano (Guatemala) through the Quantitative X-ray Map Analyzer (Q-XRMA) software. The processing strategy is based on the sequential application of the Principal Components Analysis and the supervised Maximum Likelihood Classification algorithms that allow us distinguishing among rock constituents (mineral phases, vesicles and glasses), quantifying their modal abundances, and identifying textural and chemical variations in a simplified and quick process. Here, the capability of the software has been applied to plagioclase crystals, whose textural and chemical complexities are faithful recorders of the physical and chemical conditions and processes controlling the evolution of the magmatic system. Plagioclase displays a variable extent of disequilibrium at the core and rim, as well as growth textures developed at different degrees of undercooling. This variability makes it very difficult to establish how many crystal populations are present in a sample, and to objectively decide whether there are crystals that can be considered representative of a population. The procedure applied in this study has proved to be effective for rapidly gathering chemical and textural data on plagioclase, and quantitatively document the distribution of crystals according to their size, shape, and compositions. Results demonstrate that the chemical and textural variability of crystals can be fully discerned at microscopic scale, and thus it can be adopted as a template for interpretation of magmatic processes.